Visual detection of chlorpyrifos pesticide residues in foodstuffs using a colorimetric indicator based on copper nanoparticles - Sheikh, Mahdieh; Shekarchizadeh, Hajar (Frontiers in Sustainable Food Systems, 2024)
Introduction Accurate and simple detection of pesticide residue amounts in food and crops is crucial for human health protection, food safety, environmental impact, trade, and consumer confidence. Methods Consequently, a colorimetric indicator based on copper nanoparticles (CuNPs) was developed for the detection of chlorpyrifos in this study. Results The prepared CuNPs-based colorimetric indicator exhibited color changes from black to green or blue in the presence of chlorpyrifos, visible to the naked eye and without the need for special equipment. An intriguing feature of this indicator was that its color turned blue for chlorpyrifos amounts below the maximum residue limit (MRL) and green for amounts exceeding the MRL. The complex formation of CuNPs with chlorpyrifos via the Cu-S bond, confirmed by FTIR, XPS, and XRD analysis, was responsible for the color change. Subsequently, the structure of CuNPs transitioned from a clustered to an aggregated state, as evident in the TEM images. The selectivity of the synthesized indicator against four other pesticides (glyphosate, malathion, diazinon, and imidacloprid) was investigated, revealing high selectivity against chlorpyrifos. Finally, the performance of the synthesized indicator was validated using real samples, demonstrating its high accuracy and sensitivity. Conclusion In summary, the prepared indicator represents a promising method for simple, cost-effective, accurate, and highly selective detection of chlorpyrifos.